Measuring Open Access in Finland - Ilva, Jyrki (Septentrio Conference Series, 2017)
In Finland the national Open Access monitoring efforts are integrated with the national data collection conducted by CSC - IT Centre for Science for the Ministry of Education and Culture. The collection of data on research publications encompasses universities, universities of applied sciences, central hospital districts and many of the state research institutes. The publication metadata is collected from the CRIS of each participating organization. A new automated data collection process was launched in 2016, but while some of the organizations update their data daily, many others still upload their data on annual basis. The data is stored in the Virta service built by CSC, and the de-duplicated publication data can be browsed at Juuli (http://www.juuli.fi), a VuFind-based discovery interface developed by the National Library of Finland. Starting from 2016, the Ministry has improved the way the OA status information is reported. There are two separate fields for indicating the OA status of each publication. One of the fields indicates whether the publication is OA via a Gold or a Hybrid channel, and the second field is used for indicating whether it has been deposited into a repository (Green OA). The OA definition used in the data collection has been made as clear as possible: The publication should be at least free to read Gold/Hybrid and Green Open Access are all accepted Embargoes are allowed for Green OA but not for Gold or Hybrid Depositing into an institutional or a subject-based repository is OK, but papers available at personal/project websites or at sites like Research Gate or Academia.edu don’t count The OA version must be peer-reviewed to qualify Although the quality of the data has improved, it is still far from perfect. Some of the organizations are putting more effort into the collection and verification of the data than others. At the moment no data is collected on the embargoes, the use of licenses or the APC costs associated with each publication. According to the current dataset for the year 2016, 28.6% of all peer-reviewed articles produced within the Finnish universities were reported as being Open Access. The amount of overlap between Gold/Hybrid and Green Open Access was higher than was expected. Only about 40% of the articles that the universities reported as being openly available via Green route were originally issued in non-OA publication channels. At the moment the share of OA publications is highest within the natural sciences (34%) and lowest in engineering and technology (20%), with medicine and health sciences, agriculture and forestry, humanities and social sciences falling in between them.